Antibiotic resistance pattern of uropathogens in urinary tract infections in children at State Referral Hospital, Falkawn, Mizoram, India - Lalhmangaihzuali, F. Elizabeth; ., Zarzoliana; Varte, Zorinsangi; Laldinmawii, Gracy (International Journal of Contemporary Pediatrics, 2018)
Background: Analysing antibiotic susceptibility pattern of uropathogens help to overcome the therapeutic difficulties created by the rising anti-microbial resistant bacteria and guides in choosing appropriate antibiotics. Hence, we aimed at evaluating the uropathogens causing urinary tract infections and study their antibiograms. Methods: Midstream urine samples were collected, cultured and appropriate biochemical tests were performed for proper identification of urinary tract pathogens in State Referral Hospital Falkawn, Mizoram, India from 1st January to 30th June 2018. Results: The most common isolated gram-negative uropathogens were Escherichia coli (40.9%), followed by Klebsiella spp. (17.6%), Proteus spp. (10.7%) and Pseudomonas spp. (3.1%). Among gram-positive organisms Enterococcus spp. (20.1%) and Staphylococcus spp. (7.6%) were grown. Urinary tract infections were more prevalent in girls (64.8%) than boys (35.2%). High level of resistance was found to amoxycillin/ampicillin by all the organisms isolated. Conclusions: Almost all the test organisms exhibited multiple antibiotic resistance. The study identified multiple antibiotics resistance by uropathogens which were earlier used as first line of treatment of UTI in children.